Anaesthesia Management Strategies for Cystotomy in Dogs - Kisya, Lintan Ayu; Vidiastuti, Dian (Faculty of Veterinary Medicine Universitas Brawijaya, 2023)
Geriatric and Portosystemic shunts could increase the risk of anaesthetic drug toxicity during cystotomy in dogs experiencing urolithiasis. The study reviewed the use of anaesthesia in cystotomy in dogs, from case reports published during the period between 2012-2022, retreived using the Google Scholar search engine. Inclusion criteria for the review involved a detailed description of the examinations and treatments. Ten articles were reviewed and showed that the most frequently used premedication, - induction anaesthesia, and maintenance anaesthetic agents were Xylazine, Ketamine, and Isoflurane, consecutively. In geriatric cases, Atropine Sulphate, Diazepam and Xylazine were used as premedication, while Ketamine and Propofol were used as induction anaesthesia. In large breeds, Xylazine, Meloxicam, Atropine Sulphate, Diazepam, and Buprenorphine were used as premedication, while Ketamine, Diazepam, and Propofol were used as – induction anaesthesia, and Isoflurane was used as maintenance anaesthesia. Considerations in using anaesthesia in different medical conditions are discussed.